2021
DOI: 10.3390/cancers13020203
|View full text |Cite
|
Sign up to set email alerts
|

ASCT2 and LAT1 Contribution to the Hallmarks of Cancer: From a Molecular Perspective to Clinical Translation

Abstract: The role of the amino acid transporters ASCT2 and LAT1 in cancer has been explored throughout the years. In this review, we report their impact on the hallmarks of cancer, as well as their clinical significance. Overall, both proteins have been associated with cell death resistance through dysregulation of caspases and sustainment of proliferative signaling through mTOR activation. Furthermore, ASCT2 appears to play an important role in cellular energetics regulation, whereas LAT1 expression is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 185 publications
(175 reference statements)
0
24
0
Order By: Relevance
“…While outside of the scope of this review, there are several fuel sources aside from NEAA not considered here that contribute to metabolic vulnerabilities, including glucose, essential amino acids, fatty acids, lactate, and acetate (8)(9)(10)(11). Furthermore, additional factors, including the expression of amino acid transporters (231)(232)(233)(234)(235)(236) and the effect of stromal cells on the microenvironment, can contribute to cancer metabolism and proliferation (8). It is also clear that optimal treatment strategies will consider mechanisms of cell adaptation to nutrient stress.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…While outside of the scope of this review, there are several fuel sources aside from NEAA not considered here that contribute to metabolic vulnerabilities, including glucose, essential amino acids, fatty acids, lactate, and acetate (8)(9)(10)(11). Furthermore, additional factors, including the expression of amino acid transporters (231)(232)(233)(234)(235)(236) and the effect of stromal cells on the microenvironment, can contribute to cancer metabolism and proliferation (8). It is also clear that optimal treatment strategies will consider mechanisms of cell adaptation to nutrient stress.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, only a few are involved in malignancy including AlaSerCys (alanine-serinecysteine) transporter 2 (ASCT2), LAT1, ATB 0,+ , and SNAT2 [19]. Both ASCT2 and LAT1 expression have been associated with several hallmarks of cancer, e.g., avoiding immune destruction, activating invasion and metastasis, inducing angiogenesis, resisting cell death, sustaining proliferative signaling, and dysregulating cellular energetics [12]. These unique features have been inspiring researchers to establish ASCT2 and LAT1 as novel targets for tumor-specific delivery of appropriately designed chemotherapeutic drugs [22].…”
Section: Targeted Drugs and Targeting Abnormal Metabolism Of Cancermentioning
confidence: 99%
“…L-type Amino acid Transporter 1 (LAT1), the main transporter of large neutral branched-chain amino acids, is overexpressed in malignancies to support the increased demand for bulk protein synthesis that underpins their enhanced cell proliferation and survival [10]. LAT1 inhibition has been validated in many studies to block amino acid intake resulting in tumor growth delay, indicating that LAT1 is a valid molecular target for cancer therapy [11,12]. This review summarizes the development of JPH203 (KYT-0353), the only LAT1-selective non-transportable blocker which currently passed a phase I clinical trial [13].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of LAT1 cause enhanced nutrient absorption that is essential to rapid tumor growth in lung cancers. Inhibition of LAT1 retarded the amino acid uptake and mTOR phosphorylation, suggesting that LAT1 may act as a diagnostic biomarker or therapeutic drug target [19,20]. Recent studies indicated that treatment of anticancer drug molecules linked with the branched-chain amino acid promoiety as LAT1 recognition elements such as L-valine [21], L-tryptophan [22], and L-leucine [23], caused higher LAT1-mediated drug cellular uptake and greater anticancer activity than their parent compounds.…”
Section: Introductionmentioning
confidence: 99%